In vitro effects of linamarin, amygdalin and gossypol acetic acid on hyaluronidase activity, sperm motility and morphological abnormality in bull sperm - Tanyildizi, S; Bozkurt, T (Scientific Technical Research Council Turkey, 2004)
In vitro effects of various doses of linamarin, amygdalin and gossypol acetic acid on sperm hyaluronidase activity and the percentages of motile spermatozoa and morphology were investigated in bull sperm. Holstein bulls (n = 12) aged between 2 and 3 were used in the study. Semen samples were collected from each animal 3 times and used for incubation. The samples were divided into 5 equal parts and mixed (v/v) with linamarin at doses of 0.5, 0.75, 1 and 2 muM, with amygdalin at doses of 0.4, 0.8, 1 and 2 muM and with gossypol acetic acid at doses of 2.5, 5, 10 and 20 muM. The colorimetric method based on the liberation of saccharides with N-acetylglucosamine end-groups from hyaluronic acid was used for the determination of semen hyaluronidase activity in this study. Sperm motility and morphology were assessed under a phase-contrast microscope. The incubation of the 3 compounds with sperm caused significant decreases in spermatozoa motility (P < 0.001) and hyaluronidase activity (P < 0.01) compared with the control group. Additionally, gossypol acetic acid produced a significant (P < 0.001) increase in the rate of abnormal spermatozoa during the incubation period. These results showed that linamarin, amygdalin and gossypol acetic acid have deleterious effects on bull spermatozoa in a dose-dependent manner.
Keywords: cyanogenic glycosides; hyaluronidase; motility; bull; semen